ECCENTRIC PEAK TORQUE OF THE KNEE FLEXORS AND EXTENSORS RELATES TO BACKWARD SOMERSAULT HEIGHT IN FEMALE JUNIOR ARTISTIC GYMNASTS - Sebastian Möck; Alina Korrmann; Petra Nissinen; Klaus Wirth (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
Artistic gymnastics consist of a high amount of jumping actions with rotations around one or more axes. To achieve an optimal flight height to perform the desired number of rotations, the movement pattern and the floor characteristics have to be concerted optimally. To account for the required leg stiffness to utilize the floor's elasticity, the leg musculature has to generate high forces during the ground contact in an eccentric manner. Thus, eccentric strength of the knee musculature might play an important role for somersault height and run-up velocity in the vault. We investigated the correlation of eccentric peak torque of the knee flexors and extensors and vertical jumping height with backward somersault height and sprinting velocity in female junior artistic gymnasts. The results showed medium to strong, significant correlations between eccentric peak torque and backward somersault height as well as sprinting velocity. Vertical jumping height revealed significant correlations with somersault height and sprinting velocity. Eccentric strength seems to play an important role in joint stiffness regulation to utilize the elastic recoil of gymnastic floors and springboards. In the sprint approaching the vault, the same mechanism seems apparent and is in accordance with findings regarding the sprint in different sports.